The prevalence of right‐sided colonic diverticulosis in a New Zealand population. Issue 10 (14th June 2021) - Turner, Greg A.; O'Grady, Michael J.; Senadeera, Sajith C.; Wakeman, Chris J.; McCombie, Andrew; Purcell, Rachel V.; Frizelle, Frank A.
Abstract: Background: Once considered to be a congenital condition, the epidemiology of right‐sided colonic diverticulosis (RCD) is evolving. Acute diverticulitis (AD) is a complication of RCD which is frequently misdiagnosed as appendicitis, resulting in unnecessary surgery, as there is strong evidence supporting medical management for right‐sided AD. In general, the incidence of AD correlates with the prevalence of RCD, which shows marked geographic variation. Few data reporting RCD prevalence come from Western countries, so the aim of this study is to define the prevalence of RCD in a New Zealand population. Methods: Independent review of the imaging from 1000 consecutive patients undergoing a computed tomography Kidney/Ureter/Bladder scan for suspected urolithiasis at Christchurch Hospital between January and November 2017 was undertaken, to determine the presence or absence, and distribution of colonic diverticulosis. Patients were excluded if they had a history of colonic resection, known IBD, or were less than 18‐years old. Results: Thirty‐one patients were excluded, leaving 969 eligible patients. Overall, 95 patients (9.8%) had RCD identified. The prevalence of RCD increased significantly with advancing age, being present in 2.3% of those aged 18–29, increasing to 20.3% in those greater than 70‐years old ( p < 0.001). Conclusion: The prevalence of RCD in a New Zealand population is relatively high and increases significantly with age. This adds support to the role of cross‐sectional imaging in the evaluation of suspected appendicitis, to exclude right‐sided AD. The association with advancing age supports RCD being an acquired condition rather than a congenital condition as was previously thought. Abstract : The prevalence of right‐sided colonic diverticulosis varies markedly around the world. Few published data describe the prevalence in Western countries, this study aims to evaluate the prevalence of right‐sided diverticulosis in New Zealand.